Understanding and responding to coercive control: lessons learned from England and Wales - Barlow, Charlotte (Criminalising coercive control, 2024)
Coercive and controlling behaviours were criminalised in England and Wales as part of section 76 of the Serious Crime Act 2015. There has been consequent growing academic interest and critique of coercive control as a legislative concept. This chapter aims to extend this discussion by exploring police responses to coercive control, informed by empirical data from the author’s British Academy funded project. The chapter considers how the idea of coercive control is utilised, responded to and understood in practice by police officers. The chapter compares police officers’ perceptions to the lived experiences of victim-survivors, exploring the ways in which opportunities for identifying and understanding the harms of coercive control were often missed by police officers. The chapter concludes with a discussion of the limits of criminalisation approaches in providing safety for women and children, advocating the need for holistic policy responses.